Hvad er professionsforskning? - Martin Blok Johansen; Jan Thorhauge Frederiksen (Tidsskrift for Professionsstudier, 2020)
This paper presents a discussion of what research in professions and professional work means, both generally, and in a Danish context. Initially we present a summary of the origins of the term profession, and the oldest occupations understood to be professions. Central questions when defining this origin is what constitutes the base of professional knowledge and whether such a base is specific to each profession. However, what such knowledge may be has proven hard to agree on, since such knowledge is what research in professions and professional work strive to produce. The paper instead proposes a different way to describe and categorize research in professions, which does not presume any one definition of neither profession nor knowledge. Instead, we suggest summarizing the different research practices found in the field, by way of three axes of difference: 1. Research in professions for – describing the different institutions and agents for whom the research is being produced. 2. Research in professions through – describing the different theoretical perspectives and assumptions upon which the research is based. Finally 3. Research in professions withdescribing the empirical methods and methodologies, which the research employs. On each axis, we exemplify a number of positions found in the field of research in professions. In conclusion, the paper points out correlations between positions on the three axes, which are indicative of the debates and struggles taking place in the field of research today.